Android-based "MamaKIA" Educational Media Development Application for Pregnancy Midwifery Care - Sarita, Sultina; Yustiari, Yustiari; Esti Handayani, Tinuk; Dolofu, Muliati; Asi, Melania (Poltekita : Jurnal Ilmu Kesehatan, 2023)
An Android-based pregnancy care application designed and adapted to the needs of pregnant women is part of efforts to encourage sustainable midwifery care, which is expected to make it easier to convey, understand, and apply because it is in accordance with current client needs. This research aims to develop android-based educational media for midwifery care. The development of Android-based Midwifery Care Education Media was carried out using a research and development approach consisting of a preliminary study stage consisting of a literature study and field study (two respondents), and product development consisting of product design and media expert validation testing. (one respondent), material experts (one respondent), and application trials by community health center midwives in the work area of the Konawe District Health Service (35 respondents) who were selected using purposive sampling. Research data were collected using questionnaires, and quantitative and qualitative analyses were conducted. The validation results from media experts obtained a score of 69.47% in the feasible category and 98.33% from material experts in the very appropriate category, and the test results from 35 respondents obtained a score of 92.86%, including the very appropriate category. The Android-based educational media application developed for midwifery care is very suitable for use and needs to be tested for its effectiveness in midwifery care during pregnancy. The "Mama KIA" application is very feasible in terms of materials, media, and testing and meets the requirements for midwifery care by midwives.